Smugglers’ blues: Airport drug investigations - Givan, Richard E. (American journal of criminal justice, 1986)
This article examines the Fourth Amendment problems inherent in detaining and searching commercial air travelers for smuggled drugs. Considered are problems involving the drug courier’s profile, the levels of encounters involved in the investigations, and canine sniffs of luggage.